Dos fatos e suas histórias em crônicas de Rubem Braga e reportagens televisivas de Marcelo Canellas - Melo, Mila Leal Correia (2019)
In this work, we present a study about literature and journalism from the analysis of specificities that approximate and/or differentiate chronicles of Rubem Braga and television reports of Marcelo Canellas. For this, we selected six chronicles and four reports that bring cases of daily life that gained special meanings and aesthetic expressiveness from the narratives of the two authors and facts and stories that can favor analyzes and reflections. We searched for a bibliographical survey about the definitions and characteristics of the chronicle, based on the theoretical studies of Antonio Candido (1992), Afrânio Coutinho (2003), Davi Arrigucci Júnior (1999) and Massaud Moisés (1998), and about the concepts and definitions of reporting and its role in journalism, using theories of Cremilda Medina (1988), José Marques de Melo (2010), Felipe Pena (2008) and Nilson Lage (2017). We analyze the content of the chronicles and reports from the perspective of the characters, who are conductors of the stories, and we observe that Braga and Canellas deal with convergent themes and construct narratives with subjective questions, generating deep reflections in the reader and the viewer. We reaffirm the relationship between literature and journalism and chronicle and reporting and identify elements that approximate the narratives studied.